2015
DOI: 10.4067/s0718-19572015000300005
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional condition and gonad development of juvenile and subadult California spiny lobster Panulirus interruptus in two habitats

Abstract: Resumen.-Se analizó la condición nutricional y el desarrollo gonádico de juveniles y sub-adultos de langosta roja (Panulirus interruptus) en 2 sitios de la Península de Baja California cercanos geográficamente, pero con condiciones ambientales contrastantes, el más norteño con condiciones subtropicales y el sureño con condiciones semitempladas. Se estimaron el índice hepatosomático y el índice refractivo de la sangre, y se cuantificaron las proteínas, lípi dos y carbohidratos del hepatopáncreas en 62 langostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…BRI is a proxy for physiological condition because hemolymph density is positively correlated with protein concentration in the serum of crustaceans (Lorenzon et al, 2011). However, as the molt cycle affects BRI (Rodríguez-García et al, 2015), we cut the distal third of one pleopod from each lobster to determine the molt stage by microscopy (Lyle and MacDonald, 1983). Only lobsters in intermolt (stage C of Drach's scale) were used to estimate BRI.…”
Section: Indices Of Nutritional Conditionmentioning
confidence: 99%
“…BRI is a proxy for physiological condition because hemolymph density is positively correlated with protein concentration in the serum of crustaceans (Lorenzon et al, 2011). However, as the molt cycle affects BRI (Rodríguez-García et al, 2015), we cut the distal third of one pleopod from each lobster to determine the molt stage by microscopy (Lyle and MacDonald, 1983). Only lobsters in intermolt (stage C of Drach's scale) were used to estimate BRI.…”
Section: Indices Of Nutritional Conditionmentioning
confidence: 99%
“…Additionally, a close relationship between the physiological condition of the broodstock and their reproductive success has been demonstrated for marine organisms including lobsters (Agnalt 2008;Moland et al 2010). More specifically, it was demonstrated that the inclusion of specific phospholipids in formulated feeds improved the nutritional status of the broodstock, gonad development, and egg and larvae quality (Navas et al 1997;Rodríguez-García et al 2015). Yet, to the best of our knowledge, there are no published studies on the ontogenetic changes in lipid class composition during larval development for H. gammarus.…”
Section: Introductionmentioning
confidence: 97%